Chemical Compounds and Antibacterial Activity of Thymus Vulgaris Leaves’ Ethanolic Extract Against Salmonella typhimurium: Thymus vulgaris Against Salmonella typhimurium - Abousouh, Emad Khaleefah; Endharti, Agustina Tri; Santoso, Sanarto; Santosaningsih, Dewi (Journal of Tropical Life Science, 2024)
Invasive non-typhoidal Salmonella is an important pathogen that causes life-threatening bloodstream infections. Antibiotic resistance in non-typhoidal Salmonella has emerged as a result of the increasing use of antibiotics; therefore, an alternative source of therapeutic agents is required. This study aimed to investigate the active compound and antibacterial activity of Thymus vulgaris leaves’ ethanolic extract against Salmonella typhimurium. Thin-layer chromatography was performed to identify the active compound in the ethanolic extract of T. vulgaris leaves. The antibiotic effect of the extract was carried out by agar dilution assay using the following concentrations: 0%, 2.5%, 5.0%, 7.5%, 10.0%, 12.5%, and 15.0% (w/v). Thymol and carvacrol were detected in the thin-layer chromatography. The minimum inhibitory concentration of the extract was 10.0% (w/v). In conclusion, T. vulgaris leaves’ ethanolic extract demonstrated antimicrobial activity against S. typhimurium. Further investigation is required to analyze the role of thymol and carvacrol as active compounds against S. typhimurium.